Sustainability, urbanization and civilizations: focus on Spain - Fédorova, Katerina (Reflexión Política, 2016)
The problems that divide people - interreligious, interethnic, intercultural conflicts – slow down the reaction of the world community for solving common global problems, which should unite humanity. In the context of global development issues, it is emphasized on the role of Spain in the dialogue between civilizations; its activities within the framework of Club of Rome; its experience in smart urbanization and ways to achieve sustainable development.